2014
DOI: 10.1007/s11892-013-0455-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Basis of Ethnic Differences in Diabetes Risk in Overweight and Obese Youth

Abstract: The global pandemic of childhood obesity has led to increased risk for prediabetes and type 2 diabetes mellitus (T2DM). Studies have shown decreased insulin sensitivity and/or secretion with increasing adiposity and consistently observed greater risk for T2DM in obese, non-Caucasian youth. In the current review we describe recent advances in understanding how obesity and metabolic status in children and adolescents confers various risk profiles for T2DM among Latinos, African-Americans, Caucasians, Asians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 93 publications
(123 reference statements)
3
21
0
Order By: Relevance
“…In this study of WE and BWA men with early T2D, we investigated ethnic differences in hepatic fat and its relationship with hepatic insulin sensitivity and insulin clearance. Consistent with published data, 13 BWA men had lower IHL and VAT. We found additional ethnic differences in relationships between IHL and hepatic insulin sensitivity and insulin clearance, whereby in WE men IHL was inversely related to basal hepatic insulin sensitivity and whole-body insulin sensitivity, which was not the case in BWA men.…”
Section: Discussionsupporting
confidence: 91%
“…In this study of WE and BWA men with early T2D, we investigated ethnic differences in hepatic fat and its relationship with hepatic insulin sensitivity and insulin clearance. Consistent with published data, 13 BWA men had lower IHL and VAT. We found additional ethnic differences in relationships between IHL and hepatic insulin sensitivity and insulin clearance, whereby in WE men IHL was inversely related to basal hepatic insulin sensitivity and whole-body insulin sensitivity, which was not the case in BWA men.…”
Section: Discussionsupporting
confidence: 91%
“…[43] Previous studies have reported the presence of racial and ethnic differences in DXA measured bone mass of children. [4447] However, few studies have examined the effect of race and ethnicity on measures of bone geometry and strength by pQCT.…”
Section: Discussionmentioning
confidence: 99%
“…In black populations, the majority of studies have been conducted in adolescent cohorts, with a focus on obese populations without diabetes [65,66]. Visceral fat, liver and pancreatic fat have been reported to be lower in black populations compared with their white counterparts [65,67]. In a review of ethnic differences in the prevalence of non-alcoholic fatty liver disease, Pan et al [68] found several studies consistently reporting a significantly lower prevalence of non-alcoholic fatty liver disease in black compared with white populations.…”
Section: Ethnic Differences In the Pathophysiology Of Diabetesmentioning
confidence: 99%
“…In a review of ethnic differences in the prevalence of non-alcoholic fatty liver disease, Pan et al [68] found several studies consistently reporting a significantly lower prevalence of non-alcoholic fatty liver disease in black compared with white populations. However, there is evidence that black populations may be more sensitive to the negative effects of liver fat accumulation [65]. In adults, contradictory findings have been reported; liver fat has been found to be inversely associated with hepatic insulin sensitivity in black but not white women [69], however, the opposite was found in black vs. white men, where liver fat was inversely associated with hepatic insulin sensitivity in white but not black men [70].…”
Section: Ethnic Differences In the Pathophysiology Of Diabetesmentioning
confidence: 99%